Poplarism - Lansbury, Edgar (London : Independent Labour Party)
1924 1924 1920s 8 pages PRECAUTIONS AGAINST DISHONESTY. Now let us examine some of the work of the Guardians. In every branch, this work is done with care and efficiency. We take more than the usual number of precautions to guard against dishonesty on the part of officers and recipients of relief. Occasionally we are robbed, but that is because no precaution is infallible and because all men are human. Our expenditure is high, but this is not due to wasteful methods, or to something specially sinister in Poplar finance. It is due to our enormous load of poverty. There are tables of administrative costs (much too long to include in this article) published by the London County Council that will bear out my contention that Poplar's administration costs are among the lowest in London. THE POPLAR SCALE OF RELIEF. The general impression is that the Poplar scale of relief is wasteful and extravagant and that the Guardians themselves are afraid to publish or defend it. We certainly do not exhibit our scale as an example of our good work, for, although more generous than that paid by other Guardians, it is still mean and inadequate. The following is the scale employed in relieving able-bodied unemployed persons :— Adults not living with parents 12/6 a week. Married couples or two adults living together 20/- „ Ditto, with one child 26/6 „ Ditto, with two children 30/- „ Ditto, with three children 33/6 „ Ditto, with four children 36/6 „ Ditto, with five children 39/6 „ Ditto, with six or more children......... 41/- „ Plus 1/6 a week for Coal, Gas, etc. (except for lone persons). Plus the actual amount of rent paid (up to 5/- for lone persons). This scale is worked out to cover the destitute unemployed and dependent members of the household. If there are any members of the household working, the following deductions are made from the relief and form the working member's contribution to the support of his able-bodied relatives :— In respect of earnings under 15/- a week, no deduction. In respect of earnings from 15/- to 17/6 a week ... 1/- In respect of earnings from 17/6 to 20/- a week ... 2/- In respect of earnings from 20/- to 30/- a week ... 3/- and 6d. out of every 1/- of earnings above 30/-. IS THIS EXTRAVAGANCE? It will be seen that we pay 10/- a week to a boy or girl living with parents. This means little more than starvation for the child. We pay 26/6 a week (plus rent and coal) for the maintenance of a man and wife and child. This is supposed to provide food, clothes and the 4 15X/2/209/47